2011
DOI: 10.1074/jbc.m111.242529
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Calcium on Respiration and NAD(P)H Synthesis in Intact Rat Heart Mitochondria Utilizing Physiological Substrates Cannot Explain Respiratory Control in Vivo

Abstract: Mitochondrial TCA cycle dehydrogenase enzymes have been shown to be stimulated by Ca 2؉ under various substrate and ADP incubation conditions in an attempt to determine and understand the role of Ca 2؉ in maintaining energy homeostasis in working hearts. In this study, we tested the hypothesis that, at physiological temperature and 1 mM extramitochondrial free magnesium, Ca 2؉ can stimulate the overall mitochondrial NAD(P)H generation flux in rat heart mitochondria utilizing pyruvate and malate as substrates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 23 publications
6
40
0
Order By: Relevance
“…Excess [Ca 2ϩ ]m, however, opens the permeability transition pore (40, 54), a key factor in apoptosis during ischemiareperfusion injury (12)(13)(14)(15)(16)(17). These reports, together with our findings that LTHA enhances Ca 2ϩ stress-endurance and decreases Ca 2ϩ sensitivity in cardiomyocytes (52,67), lend further support to the hypothesis that the adaptive features of the mitochondria evolve with heat acclimation and are important for HACT by enhancing respiratory performance during stress.…”
supporting
confidence: 72%
“…Excess [Ca 2ϩ ]m, however, opens the permeability transition pore (40, 54), a key factor in apoptosis during ischemiareperfusion injury (12)(13)(14)(15)(16)(17). These reports, together with our findings that LTHA enhances Ca 2ϩ stress-endurance and decreases Ca 2ϩ sensitivity in cardiomyocytes (52,67), lend further support to the hypothesis that the adaptive features of the mitochondria evolve with heat acclimation and are important for HACT by enhancing respiratory performance during stress.…”
supporting
confidence: 72%
“…However, the importance of [Ca 2+ ] m on mitochondrial dehydrogenase activities is strongly dependent on the substrate used. For example, it was reported that pyruvate dehydrogenase is activated at almost 100%, regardless of the [Ca 2+ ] m , and that α-ketoglutarate dehydrogenase is a more physiologically relevant target of Ca 2+ regulation (Vinnakota et al 2011, Wan et al 1989). This means that the greatest effect of Ca 2+ on bioenergetics would be with α-ketoglutarate as the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…First, 10 mM of substrate (NaPM or KPM) to energize mitochondria may saturate the ADP-independent TCA cycle flux. In a recent study [54], it was reported that to observe an effect of increased Ca 2+ to stimulate state 3 NADH production and respiration, a low substrate concentration is necessary. Second, the substrate glutamate +malate provides a greater NADH response to increasing extra-matrix [Ca 2+ ].…”
Section: Discussionmentioning
confidence: 99%